Efektivitas Program Pelatihan Kewirausahaan bagi Tenaga Kerja Pemula di Kota Tanjungpinang - Billy Jenawi (Dialektika Publik, 2022)
The training was a proposal from Tanjungpinang City based on the potential and conditions in each kelurahan and selected based on the results of the musrenbang. In 2019 entrepreneurship training was held for novice workers, a proposal from the Kp. Bugis. This study aimed to determine the effectiveness of entrepreneurship training for novice workers carried out by the Department of Manpower, Cooperatives and Micro Enterprises, Tanjungpinang City. The type of research used is descriptive with mixed methods using quantitative and qualitative data. The strategy used is a concurrent embedded, so one method is more dominant than the other methods. In this study, quantitative methods are more prevalent than qualitative methods.The population in this study is all parties whose characteristics can be observed to be drawn as a sample. The model in the quantitative method is the entrepreneurship training participants, as many as 19 people who were selected using saturated sampling, and the example in the qualitative form or informants are the Head of Placement and Training at the Manpower Office 1 person, one person entrepreneurship training instructor, one person from the Bugis Village Village, and five trainees. Based on the results of quantitative data research, the effectiveness of entrepreneurship training programs for the workforce of Cooperatives and Micro Enterprises in Tanjungpinang City has been very effective. However, the qualitative data still found obstacles such as the delivery of training information was not widely spread by the Bugis village community, interviews had not been carried out strictly, and there were still participants who had not applied the knowledge gained from the training. Therefore, it is suggested to the stakeholders, namely the workforce office and the kelurahan to work together in disseminating and selecting participants so that they are chosen fairly. As well as for the community is expected to maximize the knowledge gained from entrepreneurship training.